Continuously Tunable Frequency and Phase Biquad Oscillator - Chivapreecha, Sorawat; Suwannawach, Piyapan (My University, 2026)
This paper presents an improvement to the performance of a biquad oscillator, which is a recursive oscillator known for its excellent long-term stability. However, a significant limitation is that the oscillation frequency cannot be changed while the system is operating. Directly changing the frequency during operation causes the amplitude of the generated signal to vary significantly, either increasing or decreasing. A zero-input response analysis is used to understand the cause of this problem and to develop a solution that allows the amplitude of the generated signal to remain constant even when the oscillation frequency is changed during operation. In addition, this paper presents a method for controlling the phase of the generated signal by using a 1st-order IIR phase shifter structure. The proposed structure is specifically designed to allow the phase of the signal at the oscillation frequency to be adjusted continuously and independently of the frequency parameter. This integrated oscillator enables real-time, independent control of both signal frequency and phase without amplitude drift, making it suitable for applications requiring precise and dynamic signal synthesis.
Keywords: allpass filter; amplitude stabilization; arbitrary phase shift; biquad oscillator; digital phase shifter; IIR filter; recursive oscillator; tunable frequency; tunable phase